2005
DOI: 10.2320/matertrans.46.259
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Gd from Chloride Solution with PC88A

Abstract: Solvent extraction experiments of Gd from chloride solution with PC88A were conducted at different extraction conditions. Solvent extraction reaction was identified from the experimental results using a graphical method, and the corresponding effective equilibrium constant was determined by analyzing the ionic equlibria in a GdCl 3 solution. In the experimental ranges investigated in this study, i.e., ½GdCl 3 0:3 kmol/m 3 , ½PC88A org 3:0 kmol/m 3 and initial pH 2:3, solvent extraction reaction of Gd with PC88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The chemistry of cation exchange ligands for REE SX has been thoroughly investigated and is well-published; equilibrium behavior is highly dependent on REE concentrations and aqueous phase pH. Although the chemistry is well understood, predicting partitioning behavior throughout a countercurrent SX circuit with complex extraction, scrubbing, and stripping cascades remains a significant challenge. Many SX separation models only predict the steady-state concentration profiles in the organic and aqueous phases across the cascade. ,, Furthermore, REE SX models utilize empirical correlations to predict extraction behavior but do not consider more complex multicomponent scrubbing equilibrium in REE separations, particularly for adjacent REE separations. ,− Scrubbing equilibria using cation exchange ligands becomes complex due to acid–metal exchange, metal–metal exchange, and equilibrium dependencies on REE concentrations, acid concentrations, and ligand concentrations. Transient SX behavior is expected to play a significant role for troubleshooting process upsets and fluctuations from upstream ore processing as well as managing startup and the approach to steady state due to impacts on process throughput, product purities, and production schedules.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of cation exchange ligands for REE SX has been thoroughly investigated and is well-published; equilibrium behavior is highly dependent on REE concentrations and aqueous phase pH. Although the chemistry is well understood, predicting partitioning behavior throughout a countercurrent SX circuit with complex extraction, scrubbing, and stripping cascades remains a significant challenge. Many SX separation models only predict the steady-state concentration profiles in the organic and aqueous phases across the cascade. ,, Furthermore, REE SX models utilize empirical correlations to predict extraction behavior but do not consider more complex multicomponent scrubbing equilibrium in REE separations, particularly for adjacent REE separations. ,− Scrubbing equilibria using cation exchange ligands becomes complex due to acid–metal exchange, metal–metal exchange, and equilibrium dependencies on REE concentrations, acid concentrations, and ligand concentrations. Transient SX behavior is expected to play a significant role for troubleshooting process upsets and fluctuations from upstream ore processing as well as managing startup and the approach to steady state due to impacts on process throughput, product purities, and production schedules.…”
Section: Introductionmentioning
confidence: 99%
“…This interest in structural applications has motivated investigation of amorphous metals as alternatives to conventional crystalline metals in foam architectures, on account of their high-strength (typically around 2 GPa in compression [3], though amorphous alloys having compressive strengths above 5 GPa have been reported [4]), corrosion resistance, and processability (low liquidus temperatures in comparison to crystalline metals of similar strength, and high viscosity allowing foaming in the supercooled liquid state [5,6]). In order for amorphous metal foams to be viable alternatives to crystalline metal foams, however, it is necessary for them to exhibit compressive ductility far in excess of monolithic amorphous metals, which are typically limited to less than 1% compressive plastic strain in the absence of geometric confinement [7], ductile reinforcement [8], or anomalouslyhigh Poisson's ratios [9]. At low to intermediate porosities (!…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that fine crystalline particles whose size and composition are similar to those of the A2 specimen were often formed during casting of the Vit-1 alloy, and that they were identified to be fcc phase (a ϭ 1.185 nm) according to transmission electron microscopy analysis. [13,14] It is likely that the fine crystalline particles in the A2 specimen are the same ones generally formed in the cast Vit-1 alloy. The presence of crystalline particles is confirmed by the X-ray diffraction data presented in Figures 5(a) and (b).…”
mentioning
confidence: 96%